Triple‐faced polypropylene: Fire retardant, thermally stable, and antioxidative. Issue 4 (7th April 2019) - Vahabi, Henri; Paran, Seyed Mohammad Reza; Shabanian, Meisam; Dumazert, Loïc; Sonnier, Rodolphe; Movahedifar, Elnaz; Zarrintaj, Payam; Saeb, Mohammad Reza
Abstract : A halogen‐free nitrogen‐rich additive was used to make polypropylene (PP) prepared for three different missions: fire retardancy, thermal stability, and antioxidative properties. The prepared additive was composed of a cyclodextrin, a nanohydroxyapatite, and a poly[[6‐[(1, 1, 3, 3, ‐tetramethylbutyl)amino]‐1, 3, 5‐triazine‐2, 4‐diyl][(2, 2, 6, 6‐tetramethyl‐4‐piperidinyl)imino]‐1, 6‐hexanediyl[2, 2, 6, 6‐tetramethyl‐4‐piperidinyl)imino] (SABO®STAB) integrated into a unique molecule, namely, BSDH. Fire retardancy performance of BSDH in PP was compared with that of 9, 10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DOPO) commercially available additive in terms of cone calorimeter results. Thermal stabilities of PP/BSDH and PP/DOPO composites were compared by changes observed in pyrolysis activation energy values measured in thermogravimetric analysis under nitrogen atmosphere at various heating rates. Flame retardancy of PP/BSDH composite was reflected in a drop in the peak of Heat Release Rate by ca . 31% with respect to neat PP. Very interestingly, the results show that BSDH additive retarded thermal oxidation of PP macromolecular chains when compared with DOPO commercially available flame retardant, as signaled by a rise in oxidation induction time value as well as an increased early‐stage activation energy needed for thermal decomposition of PP in the presence of BSDH. J. VINYL ADDIT. TECHNOL., 25:366–376, 2019. © 2019 Society of Plastics Engineers